2022
DOI: 10.1002/mcf2.10219
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sampling Methods for Maturation Stage Determination in the European Eel Anguilla anguilla

Abstract: Monitoring data is important in ecological research, but differences between and within areas or species in data collection methods could introduce bias in the analyses. Standardizing data collection is particularly important when monitoring migratory species that have a distribution that crosses several national borders. The European Eel Anguilla anguilla is an extreme example of such a species since it constitutes one stock across the entire distribution area. One important variable collected for the Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…This is corroborated by (Sundin et al. 2022), who stated that distortions by camera lenses are thought to be minimal if the focal organ is in the center of the picture.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…This is corroborated by (Sundin et al. 2022), who stated that distortions by camera lenses are thought to be minimal if the focal organ is in the center of the picture.…”
Section: Discussionmentioning
confidence: 61%
“…A likely explanation for this finding is that the delimitation between eye and the surrounding skin may sometimes be difficult to judge on fresh eels, depending on the coloration of the individual (Sundin et al. 2022). The authors further reported that defrosted samples may be easier to measure, as the delimitation is often clearer after thawing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations